2019
DOI: 10.1186/s12967-019-02174-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating omics for a better understanding of Inflammatory Bowel Disease: a step towards personalized medicine

Abstract: Background: Inflammatory Bowel Disease (IBD) is a multifactorial chronic disease. Understanding only one aspect of IBD pathogenesis does not reflect the complex nature of IBD nor will it improve its clinical management. Therefore, it is vital to dissect the interactions between the different players in IBD pathogenesis in order to understand the biology of the disease and enhance its clinical outcomes. Aims:To provide an overview of the available omics data used to assess the potential mechanisms through which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 156 publications
(219 reference statements)
2
51
0
Order By: Relevance
“…However, the available data is a valuable resource for large-scale mining of genes associated/reported with IBD. Systems biology and reductionist approaches have identified several key genes or pathways for determining and characterizing the cause and progression of IBD [ 12 , 13 ]. However, extrapolating and summarizing the results have been difficult due to the heterogeneity of datasets and experimental designs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the available data is a valuable resource for large-scale mining of genes associated/reported with IBD. Systems biology and reductionist approaches have identified several key genes or pathways for determining and characterizing the cause and progression of IBD [ 12 , 13 ]. However, extrapolating and summarizing the results have been difficult due to the heterogeneity of datasets and experimental designs.…”
Section: Resultsmentioning
confidence: 99%
“…LitLab Gene Retriever application ( https://www.acumenta.com/generetriever ) retrieves genes associated with a publication list and is useful in specific search strategies or under less known conditions, as for the case of IBDU. As IBD etiology has a major immune component [ 12 ], we focused our targeted panel by retrieving genes associated with PubMed IDs (PMIDs) supporting the association between IBD and mucosal immunity (List 5, Fig. 1 —Gene lists).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time integrated studies are needed to decipher the mechanisms underlying IBD pathogenesis. Such studies would then contribute to the development of personalized therapeutic approaches to IBD [ 97 , 98 , 99 ]. With the advent of artificial intelligence and big data, analysis of the “integratome” (from the so-called “integrated omics”) should also open new avenues of research for enteric virus infections in IBD [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The novel inhibitors ML171 and GKT136901 selectively inhibit NOX1 and NOX1/NOX4, respectively. [46][47][48][49][50] Clinical trials with 170 patients have demonstrated that the novel inhibitors are well-tolerated and non-toxic, and thus provide a good alternative for DPI. [50] In this study, we controlled for the possible unspecific effects of DPI by additionally analysing intracellular ROS levels after inhibition of NOX1 and NOX1/4 by the selective inhibitors.…”
Section: Discussionmentioning
confidence: 99%